Metal–Organic Frameworks with Target‐Specific Active Sites Switched by Photoresponsive Motifs: Efficient Adsorbents for Tailorable CO2 Capture - Jiang, Yao; Tan, Peng; Qi, Shi‐Chao; Liu, Xiao‐Qin; Yan, Jia‐Hui; Fan, Fan; Sun, Lin‐Bing (Angewandte Chemie International Edition, 2019)
Photoresponsive metal–organic frameworks (PMOFs) are of interest for tailorable CO2 adsorption. However, modulation of CO2 adsorption on PMOFs is based on steric hindrance or structural change owing to weak interactions between CO2 and active sites. It is challenging to fabricate PMOFs with strong but tailorable sites for CO2 adsorption. Now, the construction of PMOFs with target‐specific (strong) active sites is achieved by introducing tetraethylenepentamine into azobenzene‐functionalized MOFs for tailorable CO2 adsorption. Amines are specific active sites for CO2, contributing to capture CO2 selectively. Cis/trans isomerization of azobenzene motifs trigged by UV/Vis light adjusts the electrostatic potential of amines significantly, leading to exposure/shelter of amines and modulation of CO2 adsorption on strong active sites. This system enables us to design adsorption processes for CO2 capture from mixtures, which is impossible to realize by traditional PMOFs. Smart adsorbents were fabricated by introducing target‐specific active sites (amines) into photoresponsive metal–organic frameworks (PMOFs). The cis/trans isomerization of azobenzene motifs trigged by UV/Vis light irradiation adjusts the electrostatic potential of amines significantly. This leads to exposure/shelter of amines and successful modulation of CO2 adsorption on strong active sites, which is impossible to realize by traditional PMOFs.